Analisis Kelayakan Usaha Kopra Putih di Kabupaten Indragiri Hilir Menurut Perspektif Ekonomi Syariah - Muhammad Ilyas; Syahpawi Syahpawi; Jonnius Jonnius (ISLAMIC BUSINESS and FINANCE, 2022)
This study aims to determine of kopra putih according to perspective of Islamic economics and SWOT analysis of kopra putih. The subject is Farmers in Indragiri Hilir, the object is Analysis of kopra putih business in Indragiri Hilir According to perspective of Islamic Economic. The population sample uses research informants who are selected according to research (accidental sampling). The data techniques are observation, interviews, documentation study. The analysis used is descriptive qualitative. The resource aspect is sufficient, the technical & technological aspects are relatively easy and cheap, the production aspect can produce continuously, the market & marketing aspect has many markets, while the results of BEP Grade A 88 Kg, Grade B 113 Kg and Grade C 807 Kg, the financial aspect of the results of the calculation of NPV Decent Rp. 1,093,785,500> 0, IRR Accepted results of IRR> 12% pa, BC ratio can benefit because the result is 1.16%> 0.85%, PP period 13 years 7 months annual capital return. legal aspects of registered permits, and environmental friendly social & cultural aspects, new job vacancies. As for Strength, districts with the largest land area, Weaknesses in the financial aspect, Opportunities for job and Threats to unregistered permits.